Composition and in vitro gas production of whole stems and cell walls of different genotypes of pearl millet and sorghum - Zerbini, E.; Krishan, C.T.; Victor, X.V.A.; Sharma, A. (Elsevier, 2002)
The top three senescent internodes of six genotypes of pearl millet (ICMV 155 Nor 155, ICMV 155 bmr, ICMV 221, ICMH 356, ICMH 94410, NCD 2) and sorghum (CSV 15, CSH 9, local yellow, ICSV 93046, ICSV 89057, ICSV 112) were used to asses the relationship between cell walls and wall components and in vitro gas production. Walls, (nitrogen) N, total soluble sugar contents and gas production in stems of both sorghum and pearl millet were significantly different between genotypes. In pearl millet stems, lignin and esterified p-coumaric acid (pCA) were significantly different between genotypes. In sorghum, N, lignin and phenolic acids––except esterified pCA were significantly different between genotypes. Except at 12 h for sorghum, gas production of walls was significantly different between genotypes and ranked genotypes differently than gas of stems. Soluble sugars in the stems of both pearl millet and sorghum were positively correlated to gas production at 12, 24, and 36 h, and vice versa for cell walls. In pearl millet, phenolic acids were not significantly correlated with either gas production of whole stems or that of walls, with the exception of etherified pCA of walls. On the other hand, in sorghum, etherified pCA of stems and walls were negatively correlated with gas at 72 and 96 h. The significant differences of gas production between genotypes, different ranking of genotypes with the progression of the fermentation, and the gas production differences between whole stems and walls indicate the differential effect of soluble sugars and of cell wall type on the digestibility of whole stems. This study points out the need to look in greater details at the relationship and the interactions between the effects of soluble and structural carbohydrates in stovers and the genetic base that determines it. Such studies could identify the most adequate combination of traits useful in crop improvement programs taking into account feed value of stover of dual-purpose crops.